Кейс-менеджмент как метод управления в сети отрасли здравоохранения - Сороколат, Ю. В.; Садовский, Виктор Артемович; Семенченко, Галина Владимировна (НТУ "ХПИ", 2014)
В статье рассматривается кейс-менеджмент как метод формирования управленческих решений в сети отрасли здравоохранения. Проанализированы преимущества и препятствия внедрения метода кейс-менеджмента. Приведена предлагаемая классификация управленческих решений. Обоснована необходимость дальнейшего изучения метода с целью повышения качества медицинского обслуживания населения.

In article the case-management as a method of formation of administrative decisions in a network of branch of public health services is considered. Advantages and obstacles of introduction of a method of casemanagement are analysed. Offered classification of administrative decisions is resulted. Necessity of the further studying of a method for the purpose of improvement of quality of health services of the population is proved. The system of adaptive case-management (АСМ), as means of accumulation of corporate knowledge for a reuse is considered at collective work of employees. Adaptability and flexibility АСМ allows to automate medical institution business processes.
Case-management as a management method in a health protection network
Keywords: классификация; управленческое решение; медицинское обслуживание; мотивация; method; case-management; classification; administrative decision; health services